Asian Geopolitics and the US-China Rivalry, Felix Heiduk - Iraj Abid (CISS Insight Journal, 2023)
The evolving US-China competition dominates contemporary international politics. The intensifying rivalry between the two big powers has merited the attention of scholars from various fields such as international relations, foreign policy, strategic studies, and economics. Many experts are writing to explain the nature of their contestation which is impacting almost every aspect of the international system in an increasingly globalized world. This contestation is unique as the two great powers remain entangled in complex interdependence and are unable to decouple relations particularly in the economic domain.